Challenging masculinities: religious studies, men and HIV in Africa. - Chitando, Ezra; Chirongoma, Sophia (2016)
There is a growing interest in the role of men in responding to the HIV epidemic. Since the emergence of the epidemic in the 1980s, there has been greater focus on the vulnerability of women and children. This has had the effect of overlooking the role of men in the epidemic. Alternatively, there has been a tendency to blame men for violence against women and the spread of HIV. While it is clear that men are seriously implicated in the HIV epidemic, it has also become obvious that leaving them out of prevention, care and support programmes is counterproductive (Chitando 2007: 40). There is therefore need to ensure that men remain very much in the picture as nations, communities and institutions seek to provide effective responses to the epidemic. Departments of religious studies in African universities and educational institutions are being challenged to tackle the issue of men and HIV in a creative and determined manner.